2014
DOI: 10.1089/ars.2013.5816
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Proteasome Dynamics and Allostery in Drug Design

Abstract: Significance: The proteasome is the essential protease that is responsible for regulated cleavage of the bulk of intracellular proteins. Its central role in cellular physiology has been exploited in therapies against aggressive cancers where proteasome-specific competitive inhibitors that block proteasome active centers are very effectively used. However, drugs regulating this essential protease are likely to have broader clinical usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 138 publications
(197 reference statements)
0
14
0
Order By: Relevance
“…This holoenzyme is the most advanced and physiologically involved among assemblies sharing the 20S proteasome catalytic core [28]. Beyond their proteasome-binding capacity, TAT peptides have a strong cell-penetrating potential: a fragment nearly identical to TAT1, 47 Y-R 57 , was previously reported as a "cell-penetrating-peptide" with high blood-brain barrier (BBB)-passing capacity due to its structure and highly positive charge [29]. Importantly, the basic domain extracted from the HIV-1 Tat protein context is devoid of either the transactivation or E3 recruitment capability of the viral factor [26,27,30] ( Figure 1B).…”
Section: Design Of Tat Peptidesmentioning
confidence: 99%
“…This holoenzyme is the most advanced and physiologically involved among assemblies sharing the 20S proteasome catalytic core [28]. Beyond their proteasome-binding capacity, TAT peptides have a strong cell-penetrating potential: a fragment nearly identical to TAT1, 47 Y-R 57 , was previously reported as a "cell-penetrating-peptide" with high blood-brain barrier (BBB)-passing capacity due to its structure and highly positive charge [29]. Importantly, the basic domain extracted from the HIV-1 Tat protein context is devoid of either the transactivation or E3 recruitment capability of the viral factor [26,27,30] ( Figure 1B).…”
Section: Design Of Tat Peptidesmentioning
confidence: 99%
“…35 NMR studies found that the structurally similar anti-malaria drug chloroquine was found to allosterically modulate proteasome activity by binding to the α/β interface of the Thermoplasma proteasome. 36 Similarly, 5-amino-8-hydroxyquinoline (5-AHQ, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…27,38,39 It is therefore tempting to speculate that at least some of these noncovalent, nonpeptidic quinolines may occupy a common allosteric binding site. 35 …”
Section: Introductionmentioning
confidence: 99%
“…A distinctive feature of the proteolytic subunits is that during assembly, b1, b2, and b5 can be replaced by b1i, b2i and b5i, respectively (155). Proteasomes cleave polypeptides after acidic (b1), alkaline (b2), and hydrophobic (b5) amino-acid residues, which are widely referred to as caspase-, trypsin-, and chymotrypsin-like activity, respectively (67,78,160). Notably, differential incorporation of the proteolytic subunits affects the kinetics for cleaving polypeptides.…”
Section: S Proteasome Inhibitionmentioning
confidence: 99%
“…To see this illustration in color, the reader is referred to the web version of this article at www.liebertpub.com/ars apparent inhibitory effect, induced expression and de novo assembly of proteasome complexes is observed after inhibition, but the inhibitory effect prevails (145). Allosteric drugs may have distinct advantages compared with irreversible and competitive proteasome inhibitors, such as higher versatility in targeting sites, but proteasome allostery is poorly understood (67). For research and clinical purposes, further specialization of inhibitors to differentiate between proteasome subpopulations is an ongoing endeavor with major achievements being accomplished over the past few years (97,103,121,151).…”
Section: S Proteasome Inhibitionmentioning
confidence: 99%